A leap of faith: building the trust in human biobanks - Zhang, Yi; Liao, Bohua; Lei, Ruipeng (Frontiers in Genetics, 2023)
Background: Human Biobanks are an essential resource for contemporary medical research, crucial in treating and preventing human diseases and improving health. Public trust in Human Biobanks is a vital social prerequisite for their continued operation and related research.Methods: Drawing on the "leap of faith" theory proposed by Georg Simmel and Guido Möllering, this paper first examines the relationship between public trust and Human Biobanks and the process through which such trust is established. Subsequently, based on the results of this analysis, targeted policy recommendations are put forward to consolidate or enhance public trust in Human Biobanks.Results: Public trust in Human Biobanks stems from certain "good reasons," through which uncertainty and vulnerability are "suspended" by faith, leading to a leap toward the "land of expectations." In this progress, the critical factors in building and enhancing public trust in Human Biobanks are the public's propensity to trust, the inherent trustworthiness of Human Biobanks, and the security and interactivity of the trust environment.Public trust in Human Biobanks cannot be determined by any universal formula, as it is influenced by many factors, including intangible elements such as faith that defy empirical understanding. Nonetheless, public trust in Human Biobanks can be enhanced through measures such as fostering the public's propensity to trust, enhancing the inherent trustworthiness of Human Biobanks, establishing structural safeguards for the trust environment through ethical norms, systems, and supervision, and promoting public participation.